Parental Adherence to Prevent Unintentional Home Injuries among Children in a Community of Bhaktapur, Nepal - Chhetri, Bima Thapa; Rai, Nabina (Journal of Karnali Academy of Health Sciences, 2023)
Background: Unintentional injuries are the serious worldwide public health problem directing to mortality, morbidity, disability, economic stress to health care system and household level. Curious nature of children to learn new skills around the home premises can be harmful sometime. Household injuries are often fatal but are prevantable. The study was conducted to analyse the level of parental adherence to prevent unintentional injuries among under five children and its association between independent variables.Methods: An analytical cross sectional research design was conducted in Madhyapur Thimi Municipality, Bode- 8, Bhaktapur, Nepal among 220 parents. Data was collected in August 2021 by using non-probability purposive sampling technique. A semi-structured questionnaire was self developed, it was pretested and was used for data collection.Results: The study suggests that majority (65.9%) of the respondents had more level of adherence and 34.1% had less level of adherence regarding unintentional injury prevention. Level of parental adherence was significantly associated with religion (p=0.048), number of siblings (p=0.045), number of floors (p=0.047) and number of rooms in the house (p=0.046).Conclusion: The study concludes that parents were able to maintain more level of adherence regarding injury prevention among children. Parental experience on injuries helps to prevent its occurrence in the future.